WhatsApp as Shadow Learning Management System: How University Teachers in Pakistan Build Parallel Pedagogical Infrastructure under Institutional Prohibition - Ilyas, Muhammad Tayyab; Mercader, Cristina; Bosco, Alejandra (ACADEMIA International Journal for Social Sciences, 2026)
Learning management systems are usually discussed as institutional choices: platforms a university adopts, configures, and supports. This paper examines what happens when the formal LMS is absent, unreliable, or actively prohibited, and teachers build a functional substitute from the mobile messaging tools they already carry. Drawing on an explanatory sequential mixed-methods study in a Pakistani public university (N=127 survey respondents; N=32 interviews), the analysis focuses on how teachers with low and medium digital competence use WhatsApp to perform the core pedagogical work that their institutional systems cannot sustain. Findings reveal a three-layer shadow architecture. Teachers first use WhatsApp as infrastructural backup, sending materials in advance against the likelihood of classroom equipment failure. When direct contact with students is prohibited, teachers route communication through class representatives, preserving function while producing plausible deniability. Cross-institutional peer networks and Sci-Hub fill gaps left by inadequate database subscriptions. Reading these practices through Behrens' shadow systems, Alter's workaround theory, and de Certeau's tactical practice, the paper argues that WhatsApp operates in Pakistani higher education not as an informal supplement but as a functional LMS. The persistence of this shadow layer is diagnostic: it indexes the specific failures of formal provision rather than the deficiencies of individual teachers.